Implementation of a program to improve influenza vaccination rates among medical students: a comparative study involving two university affiliated hospitals - Saro-Buendía, Miguel; Marrero-Sánchez, Ángel; García-Ruiz de Morales, Daniel; Chiara-Graciani, Guillermo; Coderch-Carretero, Jaime; Pérez-Jacoiste Asín, María Asunción; Silva, José Tiago; Fernández-Ruiz, Mario; Arrazola, Pilar; Aguado, José María; López-Medrano, Francisco (Human Vaccines & Immunotherapeutics, 2021)
Background and objectives: Influenza vaccination rates among medical students (MSs) are below the standards recommended in hospitals where influenza vaccination is not mandatory. We carried out a comparative study in two Spanish university hospitals to reassert this fact and evaluated the impact on vaccination rates of a specific program aimed at promoting influenza vaccination among MSs. Methods: A descriptive cross-sectional study was performed describing influenza vaccination rates and motivations for vaccination during the 2017/18 campaign among MSs in two hospitals affiliated to the same university. We subsequently performed a community-based intervention study during the 2018/19 campaign evaluating the impact of a strategy for promoting influenza vaccination, comparing the hospital where the intervention took place (hospital A) with the one where it did not take place (hospital B). Results: During de 2017/18 campaign the overall influenza vaccination rate was 44.8%, with no differences between hospitals A and B (difference: 3.9%; 95% CI: −4.36-12.16; p-value = .4). During the 2018/19 campaign, vaccination rate increased to 76.4% in hospital A, with significant differences compared with the previous campaign in the same hospital (29.8%; OR 5.00; 95% CI: 3.14-8.3; p-value = .0001) and with that observed in hospital B in the same campaign (21.1%; 95% CI: 13.38-28.82; p-value <.001). Conclusions: Influenza vaccination rates among MSs in two Spanish university affiliated hospitals were below the recommended standards. A new reproducible strategy for promoting influenza vaccination with a specific approach toward MSs achieved a significant improvement in vaccination rate.